The effect of an educational curriculum with practical demonstrations on the accuracy of volleyball decision-making for fourth-stage students of the College of Physical Education and Sports Sciences, Diyala University - Mohammed waleed shehab, Ahmed Jalel Ismael , Aseel ibraheem shehab (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The current study aimed at using practical offers in developing legal knowledge in the accuracy of decision-making for the basic rules of the game of volleyball for students of the fourth stage of the Faculty of Physical Education and Sports Sciences at Diyala University, and this development is measured by the efficiency of modern methods and methods, and scientific development has added many new methods and means that enable The teacher can benefit from it in preparing areas of expertise for learners so that they are prepared with high efficiency, if the teacher's task is no longer limited to explaining, clarifying and following traditional methods in educational science, but rather the first and main task is to draw a blueprint for the educational unit strategies, in which educational methods work to achieve limited goals The aim of learning in physical education and sports science is to prepare students to reach their simple abilities to the highest possible level, and in order to achieve these goals, the educational curriculum vocabulary must be developed according to scientific foundations and strategies commensurate with the modern variables of students' ideas. Therefore, scientific presentations are one of the strategies that make students able to Transferring experience to others, which makes the information stored in the learner's memory For a long time, it also helps students to develop thinking skills and information retrieval, and scientific presentations are performed by the method of presentation in front of the students, which is a learning method that the teacher performs to present a scientific fact or concept or generalization of a specific or to present a specific technological skill such as publishing and installation tools and so on to achieve educational goals Certain sports, and among the sports that are taught in the colleges of physical education and sports science, volleyball is one of the differential games that have witnessed a wide development that included all its vocabulary. Accuracy in performance requires us to find alternative methods and modern methods in order to keep pace with these developments of the game.